Palestine papers, 1917-1922 : seeds of conflict - Ingrams, Doreen (London : Eland, 2009)
This historical research gives the inside story of how the Balfour Declaration of 1917 was transformed, by 1922, into the British Mandate of Palestine with its impossible dual objective of fostering Zionism and protecting the rights of the native Palestinians.
"First published by John Murray in 1972"--T.p. verso.
Includes bibliographical references (p. 184-189) and index.
Keywords: Mandates -- Palestine; Palestine -- History -- 1917-1948 -- Sources; Palestine -- History -- 1917-1948.